Stroke risk, phenotypes, and death in COVID-19: Systematic review and newly reported cases. (15th December 2020) - Fridman, Sebastian; Bres Bullrich, Maria; Jimenez-Ruiz, Amado; Costantini, Pablo; Shah, Palak; Just, Caroline; Vela-Duarte, Daniel; Linfante, Italo; Sharifi-Razavi, Athena; Karimi, Narges; Bagur, Rodrigo; Debicki, Derek B.; et al.
Abstract : Objectives: To investigate the hypothesis that strokes occurring in patients with coronavirus disease 2019 (COVID-19) have distinctive features, we investigated stroke risk, clinical phenotypes, and outcomes in this population. Methods: We performed a systematic search resulting in 10 studies reporting stroke frequency among patients with COVID-19, which were pooled with 1 unpublished series from Canada. We applied random-effects meta-analyses to estimate the proportion of stroke among COVID-19. We performed an additional systematic search for cases series of stroke in patients with COVID-19 (n = 125), and we pooled these data with 35 unpublished cases from Canada, the United States, and Iran. We analyzed clinical characteristics and in-hospital mortality stratified into age groups (<50, 50–70, >70 years). We applied cluster analyses to identify specific clinical phenotypes and their relationship with death. Results: The proportions of patients with COVID-19 with stroke (1.8%, 95% confidence interval [CI] 0.9%–3.7%) and in-hospital mortality (34.4%, 95% CI 27.2%–42.4%) were exceedingly high. Mortality was 67% lower in patients <50 years of age relative to those >70 years of age (odds ratio [OR] 0.33, 95% CI 0.12–0.94, p = 0.039). Large vessel occlusion was twice as frequent (46.9%) as previously reported and was high across all age groups, even in the absence of risk factors or comorbid conditions. A clinical phenotype characterized by older age, a higher burden of comorbid conditions, and severe COVID-19 respiratory symptoms was associated with the highest in-hospital mortality (58.6%) and a 3 times higher risk of death than the rest of the cohort (OR 3.52, 95% CI 1.53–8.09, p = 0.003). Conclusions: Stroke is relatively frequent among patients with COVID-19 and has devastating consequences across all ages. The interplay of older age, comorbid conditions, and severity of COVID-19 respiratory symptoms is associated with an extremely elevated mortality.